1130. Ensovibep antiviral activity in ambulatory patients with COVID-19 is independent of baseline anti-SARS-CoV-2 antibodies and exhibits minimal selective pressure – Results from the placebo-controlled EMPATHY trial. (15th December 2022) - Abrishamian, Luis; Bonten, Marc; Chandra, Richa; Elango, Damodaran Solai; Fustier, Pierre; Gedif, Kinfemichael; Goncalves, Susana; Igbinadolor, Awawu; Kingsley, Jeff; Knutson, Charles G; Kukkaro, Petra; Kumarasamy, Nagalingeswaran; et al.
Abstract: Background: Ensovibep is a multi-specific DARPin (designed ankyrin repeat protein) antiviral in clinical development for treatment of COVID-19. In the Phase 2 EMPATHY study, ensovibep demonstrated greater viral load decline versus placebo. Here we report (1) the efficacy of ensovibep in patients with and without anti-SARS-CoV-2 antibodies at baseline and (2) SARS-CoV-2 mutation emergence data with treatment. Methods: Eligible ambulatory patients with ≥2 COVID-19 symptoms (onset within 7 days) and positive SARS-CoV-2 rapid antigen test on day of dosing, were randomized (1:1:1:1) to ensovibep (600, 225 or 75 mg) or placebo as single, IV infusion. Chemiluminescent immunoassays were used for antibody detection (SARS-CoV-2 S1/S2 IgG and SARS-CoV-2 IgM). A pre-specified subgroup analysis was performed based on baseline anti-SARS-CoV-2 antibody status. Analysis of changes in viral genome from baseline to post baseline was performed to evaluate treatment-emergent mutations. Results: Of the patients analyzed, 48.5% had anti-SARS-CoV-2 antibodies at baseline. Baseline log10 SARS-CoV-2 viral load (mean ±SD) was similar across groups [ensovibep (all doses) 6.5 ±1.5, placebo 6.2 ±1.5]; > 90% were infected with the Delta (B.1.617.2) variant. SARS-CoV-2 viral load reduction up to Day 8 showed similar effects in favor of ensovibep compared with placebo regardless of the presence of anti-SARS-CoV-2 antibodies (Figure 1 ). Patients in ensovibep 75 mg, 600 mg, and placebo groups had comparable incidences of emergent mutations, with a higher incidence in the 225 mg group. Based on analysis of 70% of the expected viral sequencing data, two mutations in the key binding residues of ensovibep were observed (Y489H and F486L) in a total of three patients treated with ensovibep. These patients either cleared virus by Day 8 or mutations were transient (occurred at a single time point but not later in the course of infection). Figure 1 Forest plot of estimated treatment differences and associated 95% confidence intervals in time-weighted change from baseline in log10 SARS-CoV-2 viral load through Day 8 by subgroups for the presence of anti-SARS-CoV-2 antibodies (SARS-CoV-2 S1/S2 IgG and/or SARS-CoV-2 IgM) at baseline. Conclusion: Ensovibep effectively reduces SARS-CoV-2 viral load regardless of the presence of anti-SARS-CoV-2 antibodies at baseline. Furthermore, there were no emerging mutations of concern, indicating that a single dose administration of ensovibep is associated with minimal selective pressure. Disclosures: Marc Bonten, MD, PhD, Astra-Zeneca: Advisor/Consultant|Janssen: Advisor/Consultant|Merck: Advisor/Consultant|Novartis: Advisor/Consultant Richa Chandra, MD, Novartis Pharmaceuticals Corporation: Employee Damodaran Solai Elango, MD, Novartis Healthcare Pvt Ltd: Employee Pierre Fustier, PhD, Molecular Partners AG: Employee Kinfemichael Gedif, PhD, Novartis Pharmaceuticals Corporation: Employee Susana Goncalves, MD, Novartis Pharma AG: Employee Awawu Igbinadolor, MD, Novartis: Awawu Igbinadolor reports financial support from different pharmaceutical companies and organizations Jeff Kingsley, DO, MBA, CPI, FACRP, Centricity Research: Other Charles G. Knutson, PhD, Novartis Institutes for BioMedical Research: Employee Petra Kukkaro, PhD, Novartis Pharma AG: Employee Nagalingeswaran Kumarasamy, MD, Novartis: Nagalingeswaran Kumarasamy reports financial support from different pharmaceutical companies and organizations Philippe Legenne, MD, Molecular Partners AG: Employee Martha Mekebeb-Reuter, MD, Novartis: Martha Mekebeb-Reuter reports financial support from different pharmaceutical companies and organizations Krishnan Ramanathan, MD, Novartis Pharma AG: Employee Evgeniya Reshetnyak, PhD, Novartis Pharmaceuticals Corporation: Employee Michael Robinson, PhD, Novartis Institute for Tropical Disease: Employee Jennifer Rosa, MD, Novartis: Jennifer Rosa reports financial support from different pharmaceutical companies and organizations Marianne Soergel, MD, Molecular Partners AG: Employee Vaia Stavropoulou, PhD, Molecular Partners AG: Employee Nina Stojcheva, PhD, Molecular Partners AG: Employee Michael T. Stumpp, PhD, Molecular Partners AG: Employee Andreas Tietz, MD, Novartis Pharma AG: Employee Xiaojun Zhao, PhD, Novartis Institutes for BioMedical Research: Employee Zhaojie Zhang, PhD, 8. Novartis Institutes for BioMedical Research: Employee.